1971
DOI: 10.1177/003693307101600504
|View full text |Cite
|
Sign up to set email alerts
|

Severe Salmonella Gastroenteritis Associated with Hypochlorhydria

Abstract: An unusually severe and prolonged salmonella enteritis is described in 6 adults; 5 had previously undergone gastric surgery and one had pernicious anaemia. Possible causes are discussed but the probable common aetiological factor was deficient gastric juice. Hypo- or achlorhydric subjects appear more prone to salmonellosis and may become seriously ill as a result. Any diarrheal illness in them should be investigated by the bacteriologist before being attributed to altered physiology alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

1980
1980
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(4 citation statements)
references
References 9 publications
0
3
0
1
Order By: Relevance
“…(1) Non-typhoid salmonellosis : Before the entry of antisecretagous drugs, the best evidence for increased susceptibility to enteric infections following hypo/achlorhydria was the increased occurrence [79,80,81,82,83,84] and severity [80,85] of salmonellosis following gastric surgery inhibiting gastric acid secretion. The indications for gastric resection/gastrectomy in these studies were primarily peptic ulcer disease or gastric malignancy.…”
Section: Microbiological Consequences Of Removing Gastric Acidmentioning
confidence: 99%
“…(1) Non-typhoid salmonellosis : Before the entry of antisecretagous drugs, the best evidence for increased susceptibility to enteric infections following hypo/achlorhydria was the increased occurrence [79,80,81,82,83,84] and severity [80,85] of salmonellosis following gastric surgery inhibiting gastric acid secretion. The indications for gastric resection/gastrectomy in these studies were primarily peptic ulcer disease or gastric malignancy.…”
Section: Microbiological Consequences Of Removing Gastric Acidmentioning
confidence: 99%
“…Subsequently, several studies confirmed this association (Close et al 1960; Sokol 1965; Giannella et al 1971; Buchin et al 1980). Also the severity of the salmonellosis was found to be correlated to previous gastric resection/gastrectomy (Nordbring 1962; Gray & Trueman 1971) or to reduced gastric acid secretion (Giannella et al 1973). The indications for gastric resection/gastrectomy in these studies were primarily peptic ulcer disease or gastric malignancy.…”
mentioning
confidence: 99%
“…These adverse factors include the extremes of age, achlorhydria (Gray and Trueman, 1971), previous gastric resection (Waddel and Kunz, 1956), co-existent diseases, chronic haemolytic disease (Hook, Kaye and Gill, 1967), other debilitating disease (Mandell, Douglas and Bennett, 1979), immunosuppressive therapy (Hook,I96 1) and possibly therapy with antacids, oral antibiotics, and intestinal sedatives. Previous therapy with oral streptomycin markedly reduces the size of the infecting dose required to produce salmonella infections in animals (Miller and Bohnhoff, 1963).…”
Section: Discussionmentioning
confidence: 99%